2021
DOI: 10.1007/s11255-021-02847-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved global response outcome after intradetrusor injection of adult muscle-derived cells for the treatment of underactive bladder

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Only one previous case report and one study examined the use of stem cells to treat underactive bladder. These data were produced by the same research group [ 8 , 13 ]. The case report describes only one patient, and the stem cells had a muscular origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one previous case report and one study examined the use of stem cells to treat underactive bladder. These data were produced by the same research group [ 8 , 13 ]. The case report describes only one patient, and the stem cells had a muscular origin.…”
Section: Discussionmentioning
confidence: 99%
“…The second study, which used cells derived from autologous muscle, reported an improvement of 83% in the patients studied, although only 69% stopped using intermittent catheterization. Moreover, in both studies, the therapy was considered safe, as there were no adverse effects, including the absence of hematuria, urological emergencies and/or infections [ 8 , 13 ]. Nonetheless, importantly, despite being produced by the same group of researchers, these studies contain no standardization in the nomenclature of the type of cell that was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various clinical trials have investigated the efficacy of autologous muscle- or adipose tissue-derived MSCs in urological diseases including stress urinary incontinence and detrusor underactivity. 9 , 29 Using autologous MSCs might be safer than using allogenic MSCs, but the challenges of hampered engraftment and survival of transplanted cells remain. Large-scale production of MSCs derived from adult tissues has limits in maintaining primitive function and proliferative capacities, 11 , 12 especially if the cells are obtained from tissues of an aged donor.…”
Section: Discussionmentioning
confidence: 99%
“…The application of autologous muscle-derived mesenchymal stem cells (AMDC) has been reported in several clinical trials to treat stress urinary incontinence patients. Recently, Gilleran et al, reported the first regulatory approved clinical trial, which evaluated the safety and efficacy of intradetrusor injected AMDCs in 20 non-neurogenic DUA patients [ 29 ]. The study subjects received approximately 30 transurethral injections of 0.5 mL delivered to the bladder (125 million AMDC/15 mL).…”
Section: Discussionmentioning
confidence: 99%